Análise econômica de transporte e armazenagem de grãos: um estudo na região norte matogrossense - Ferreira, Mario Cesar Luz (1990)
The objective of this work «as to carry an economical analysis of grain 6torage and transportation in the Mato Grosso region (30 municiplaities); it also aimed to find out the storage déficit which took place there in 1987 as well as to forecast for 1995. Corn and soybean production data concerning 1987 were obtained at Fundação Cândido Rondon-MT for each municipality and the production forecast for 1995 form the C.F.P. recordings. Storage costs were discriminated in three size "modulus" either for investment or for operational cost through calculation sheets. Transportation costs were discriminated in accordance with rode types and physical qualities of grain obtained from GEIPOT. The method used was the metwork pattern. Five situations were used in this work, two of them concerning the present system (1987) and the three others concerning the future in (1995). For the present system- which is represented by situation I - the production flow was used taking into account just the existing warehouses. For the 6ituation II, the candidate warehouses were alocated, what increased two 5.000 - ton. Stores for Barra do Bugre and Várzea Grande. A reduction of 5.9% in the total transference cost was obtained for situation II. The production flow adopedt for the future system in situation III was designed just for the existing warehouses. In situation IV the designed production flow was used by alocating candidate warehouses with reduced capacity. Candidate stores with expanded capacity were alocated and the flow production designed was adopted. The final result suggests that the Network in 10 municipalities should be expanded by increasing storage capacity up to 688.000 t. The situation V suggests that Network in 4 municipalities should be expanded by increasing the storage capacity up to 500.000 t. Situation IV showed a total cost reduction of 13% when compared to situation III. When compared to situation IV, situation V showed to be as 12% lower while the total storage cost was 12% lower and was increased in 2%. These findings led to the conclusion that shorter alocation units are more profitable, bring more benefits to the farmers and increase the number of municipalities provided with stores.